The Diversity and Productivity of Indigenous Forage in Former Limestone Mining Quarry in Karst Mountain of Southern Gombong, Central Java Indonesia - Sarwanto, Doso; Prayitno, Caribu Hadi (ANIMAL PRODUCTION, 2015)
Indonesia is a country that has a lot of limestone mountains, covering 15.4 million hectares. Limestone mountains have strategic functions as limestone is used as building materials and as raw material in cement industry. Therefore, limestone mining quarry in various areas of limestone mountains in Indonesia is increasingly widespread. The biggest negative impact of limestone mining is the formed open land which is abandoned and unutilized. Changes in the ecosystem will lead to the reduced levels of diversity and productivity of indigenous forage which will ultimately reduce the performance and development of ruminants livestock kept by farmers in the mountainous region of limestone. This study aims to determine the diversity and productivity of indigenous forage on former limestone mining quarry in limestone mountains of southern Gombong. The research was conducted through survey by identifying and measuring the forage production of sample plots assigned purposively. Location of the study was divided into three categories, mild, moderate and heavy mining. Results showed that soil fertility levels in open fields of former limestone mining in southern Gombong mountains are low with total N content of 0.049 - 0.141%, total P2O5 of 0.067 - 0.133% and total K2O of 0.086 - 0.100%. The diversity of indigenous forage on mild mining was more diverse than that of moderate and heavy mining, i.e. 13 species comprising 7 grass species, 2 legumes species, and 4 species of shrubs. The most dominant species in all mining categories are Cynodon dactylon, Imperata cylindrica, Ageratum conyzoides and Mikania micrantha. The results also showed that in the open land of mild mining had the highest production of fresh and dry matter compared to that of moderate and severe mining